2014
DOI: 10.1016/j.ahj.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and vascular effects of fingolimod: Mechanistic basis and clinical implications

Abstract: Fingolimod, a sphingosine-1-phosphate receptor (S1PR) modulator, was the first oral disease-modifying therapy approved for relapsing forms of multiple sclerosis; it reduces autoreactive lymphocytes' egress from lymphoid tissues by down-regulating S1PRs. Sphingosine-1-phosphate signaling is implicated in a range of physiologic functions, and S1PRs are expressed differentially in various tissues, including the cardiovascular system. Modulation of S1PRs on cardiac cells provides an explanation for the transient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
250
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(260 citation statements)
references
References 87 publications
9
250
1
Order By: Relevance
“…A gradual dose titration regimen to minimize first-dose effects of ponesimod In humans, activation of S1P 1 receptors on cardiomyocytes during initiation of treatment with an S1P 1 R modulator leads to transient HR decreases and infrequently AV conduction delays [Peters and Alewijnse, 2007;Camm et al 2014]. These effects initially observed with the nonselective S1PR modulator fingolimod were later found to occur also with selective S1P 1 R modulators in humans.…”
Section: Current Assessment Of Ponesimod Benefit-risk In Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…A gradual dose titration regimen to minimize first-dose effects of ponesimod In humans, activation of S1P 1 receptors on cardiomyocytes during initiation of treatment with an S1P 1 R modulator leads to transient HR decreases and infrequently AV conduction delays [Peters and Alewijnse, 2007;Camm et al 2014]. These effects initially observed with the nonselective S1PR modulator fingolimod were later found to occur also with selective S1P 1 R modulators in humans.…”
Section: Current Assessment Of Ponesimod Benefit-risk In Psoriasismentioning
confidence: 99%
“…Initial studies in rodents suggested that modulation of S1P 3 R on cardiac myocytes by fingolimod was associated with a reduction of heart rate (HR) by activation of G-protein-coupled inwardly rectifying potassium channels (GIRK) that regulate pacemaker frequency, and the shape and duration of action potentials [Koyrakh et al 2005;Camm et al 2014]. Modulation of S1P 2 R and S1P 3 R on myofibroblasts by fingolimod was also shown to stimulate extracellular matrix synthesis [Sobel et al 2013].…”
mentioning
confidence: 99%
“…This same mechanism is responsible for Mobitz type 1 s-degree AV nodal block observed in 0.2% of those patients treated with fingolimod. 6,7 An increase in blood pressure is observed in patients treated with fingolimod. This increase is, on average, +2 mm Hg systolic and +1 mm Hg diastolic.…”
Section: Fingolimod's Mode Of Action and Its Cardiovascular Side Effectsmentioning
confidence: 99%
“…Data are representative of at least 3 independent experiments. 4 0 9 0 jci.org Volume 126 Number 11 November 2016 in the heart (22,27,28). The conformationally constrained FTY720 analog SH-BC-893, in contrast, could be used therapeutically, as it does not activate S1P 1 in reporter cells ( Figure 1, A and B).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting cancer metabolism by simultaneously disrupting parallel nutrient access pathways despite their activity in vitro and in animal models (21,22). Even if sphingolipids with acceptable drug properties were developed, lysosomal nutrient generation from macropinosome and/or autophagosome degradation could afford resistance, particularly in tumors with activated Ras, in which these pathways are upregulated (9,23).…”
Section: Introductionmentioning
confidence: 99%